Assessment of Error Sources in Measurements of Field pH: Effect of Operator Experience, Test Kit Differences, and Time-Of-Day - Robinson, Nathan J.; Norng, Sorn; Rees, David B.; Benke, Kurt K.; Davey, Michelle (Communications in Soil Science and Plant Analysis, 2018)
Various methods exist to measure soil pH, and while there is general agreement between the existing published laboratory and field-based methods, the latter are subject to uncertainties including test kit reliability, accuracy, precision, and environmental factors. The contribution of this study is to quantify three uncertainties that affect the conversion between field pH and laboratory pH measurements, namely operator experience, choice of test kit, and the time-of-day for measurement. Soil samples from western Victoria, representing the pH range 4.5-10.0, were used in a randomized complete block design with 10 assessors split into two groups representing experienced and inexperienced users. Statistical analysis of laboratory and field pH was based on using the Maximum Likelihood Functional Relationship (MLFR) to determine if there was any bias between the two methods. Significant differences were found between experienced and inexperienced users, and between test kits.